Propose business strategy to increase seragam harapan adek sales - Aulia Harmaylin, Novelina; Aditya Wibowo, Satya (The Indonesian Journal of Business Administration, 2019)
Abstract School participation growth in Indonesia always in high number and also followed by number of student. Growth of number of student followed by needs that must be met, one of them is school’s uniform. It shows that school’s uniform business is a great opportunity for SME. Seragam Harapan Adek is a brand that provide not only school’s uniform, but also school’s accessories, and other thing that student needs. However, Seragam Harapan Adek faces some problem, one of them is the inconsistent sales. Besides, Seragam Harapan Adek also need to figure out how to growth, aim new market, and survive in school’s uniform market competition. Conceptual framework used in this study to analyze Seragam Harapan Adek’s market conditions both external and internal. For external analysis, author use PEST analysis, porter five forces, and competitor analysis. For internal analysis, author use STP, marketing mix, VRIO analysis, and business model canvas. External and internal factor than used to determine the new marketing strategy for Seragam Harapan Adek to increase their sales. External and internal factors than used to formulate SWOT.  From SWOT’s result fund, author determine new marketing strategy. New strategy that will recommended for Seragam Harapan Adek are new STP, new marketing mix, and new business model canvas.Keywords: Business strategy, school’s uniform, SWOT, marketing mix, business model canvas